Pengaruh Gaya Kepemimpinan Transformasional, Budaya Organisasi dan Komitmen Organisasi pada Kinerja Organisasi - Perawati, Komang Mas; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 25 No 3 (2018), 2018)
The success of a company or organization to produce good performance depends on the leader. Leadership should be supported by a good organizational culture as well. The leadership style that is supported by organizational culture and high commitment can produce good organizational performance. This study aim ed to empirically examine the effect of transformational leadership style, organizational culture, and organizational commitment on organizational performance in the Savings and Loans Cooperative of Gianyar Regency. The sample determination method used was Probability Sampling with proportionate stratified random sampling technique and obtained 54 cooperatives. Multiple linear regression analysis wa s used as a data analysis technique by conducting a model feasibility test, testing the determination coefficient and t test to test the hypothesis. Study's result showed that transformational leadership style has a positive influence on organizational performance, organizational culture has a positive influence on organizational performance, and organizational commitment has no influence on organizational performance. Keywords : transformational leadership style, organizational culture, organizational   commitment, organizational performance